Erythroleukemia cells acquire an alternative mitophagy capability - Wang, Jian (Sci Rep, 2016)
Leukemia cells are superior to hematopoietic cells with a normal differentiation potential in buffering cellular stresses, but the underlying mechanisms for this leukemic advantage are not fully understood. Using CRISPR/Cas9 deletion of the canonical autophagy-essential gene Atg7, we found that erythroleukemia K562 cells are armed with two sets of autophagic machinery. Alternative mitophagy is functional regardless of whether the canonical autophagic mechanism is intact or disrupted. Although canonical autophagy defects attenuated cell cycling, proliferation and differentiation potential, the leukemia cells retained their abilities for mitochondrial clearance and for maintaining low levels of reactive oxygen species (ROS) and apoptosis. Treatment with a specific inducer of mitophagy revealed that the canonical autophagy-defective erythroleukemia cells preserved a mitophagic response. Selective induction of mitophagy was associated with the upregulation and localization of RAB9A on the mitochondrial membrane in both wild-type and Atg7(−/−) leukemia cells. When the leukemia cells were treated with the alternative autophagy inhibitor brefeldin A or when the RAB9A was knocked down, this mitophagy was prohibited. This was accompanied by elevated ROS levels and apoptosis as well as reduced DNA damage repair. Therefore, the results suggest that erythroleukemia K562 cells possess an ATG7-independent alternative mitophagic mechanism that functions even when the canonical autophagic process is impaired, thereby maintaining the ability to respond to stresses such as excessive ROS and DNA damage.